PROTECTING THE RIGHTS OF PERSONS WITH DISABILITIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article is devoted to the issue of protecting the rights of persons with disabilities, which analyzes the legal status, fundamental rights and freedoms of this category of persons, as well as mechanisms for ensuring them. The article examines the international legal framework for the rights of persons with disabilities, in particular, UN documents and national legislative norms. It also covers the principles of equality and non-discrimination, guarantees in the fields of social protection, education, labor and medical care. Methods of preventing violations of rights, judicial and administrative protection, as well as practical problems are also analyzed. The results of the study substantiate the role of persons with disabilities in society and the need to effectively ensure their rights.